127TiP PROPEL: A phase I/II trial of bempegaldesleukin (NKTR-214) in combination with pembrolizumab (pembro) in patients (pts) with advanced solid tumours. (15th December 2019) - Reck, M; Cappuzzo, F; Rodriguez-Abreu, D; Cho, D C; Schwarz, J K; Riese, M J; Gupta, A; Chan, T; Saab, R; Singel, S; Lin, W; Tagliaferri, M; et al.
Abstract: Background: Checkpoint Inhibitors (CPIs), are now part of standard treatment in many advanced solid tumors, including metastatic non-small cell lung cancer (mNSCLC). However, novel, more effective CPI combinations are needed to broaden, deepen, and prolong responses, especially for pts with poor prognostic features or negative predictive clinical factors for CPI benefit, including PD-L1 negative (-) status. Bempegaldesleukin (BEMPEG; NKTR-214) is a CD122-preferential IL-2 pathway agonist designed to provide sustained signaling through the IL-2 βγ receptor. BEMPEG + CPI has demonstrated promising efficacy and can convert PD-L1(-) tumors to PD-L1(+) in pts with multiple solid tumors (Diab A, ASCO 2018; Siefker-Radtke A, ASCO-GU 2019). Given the early efficacy data and favorable safety profile of BEMPEG + nivolumab, PROPEL will evaluate the clinical benefit, safety and tolerability of BEMPEG combined with another CPI, pembrolizumab (PEMBRO). Trial Design: This phase I/II multinational trial evaluates BEMPEG + PEMBRO in pts with locally advanced or metastatic solid tumors. There are two key components to the study: 1) Dose optimization: which includes 3 + 3 and step-up dosing (U.S. enrollment only) and will include ∼40 pts with first- and second-line melanoma, NSCLC, urothelial carcinoma, head and neck squamous cell carcinoma, and hepatocellular carcinoma, regardless of PD-L1 status; 2) Dose expansion: which includes ∼58 first-line mNSCLC pts (enrolling globally). The expansion cohort will evaluate the preliminary anti-tumor activity of BEMPEG, in combination with PEMBRO, in first-line mNSCLC, regardless of PD-L1 status (<1%, 1-49%, and >50%). The primary objectives in the dose optimization cohorts are safety and tolerability of the combination and to determine the maximum tolerated dose, recommended phase II dose and optimal dosing schedule of BEMPEG in combination with PEMBRO in locally advanced or metastatic solid tumors. The primary objective in the dose expansion cohort is objective response rate by RECIST 1.1. Enrollment is ongoing. Clinical trial identification: NCT03138889. Legal entity responsible for the study: Nektar Therapeutics. Funding: Nektar Therapeutics. Disclosure: M. Reck: Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony: Lilly; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy, Speaker Bureau / Expert testimony: Merck Sharp & Dohme; Advisory / Consultancy, Speaker Bureau / Expert testimony: Bristol-Myers Squibb; Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer Ingelheim; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony: Celgene. F. Cappuzzo: Honoraria (self), Advisory / Consultancy: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy: Clovis Oncology; Honoraria (self), Advisory / Consultancy: Pfizer; Honoraria (self), Advisory / Consultancy: Roche/Genentech; Advisory / Consultancy: Lilly. D. Rodriguez-Abreu: Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Hoffmann-La Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Bristol-Myers Squibb; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: MSD; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Boehringer-Ingelheim. D.C. Cho: Advisory / Consultancy: Puretech; Advisory / Consultancy: Nektar Therapeutics; Advisory / Consultancy: HUYA; Advisory / Consultancy: Prometheus; Advisory / Consultancy: Genentech; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Exelixis. M.J. Riese: Advisory / Consultancy: Abbvie; Advisory / Consultancy, Research grant / Funding (self): Bristol-Myers Squibb; Advisory / Consultancy: Exelixis; Advisory / Consultancy, Research grant / Funding (self): Incyte. A. Gupta: Leadership role, Employed by Nektar: Nektar Therapeutics. T. Chan: Leadership role, Employed by Nektar: Nektar Therapeutics. R. Saab: Leadership role, Employed by Nektar: Nektar Therapeutics. S. Singel: Leadership role, Employed by Nektar: Nektar Therapeutics. W. Lin: Leadership role, Employed by Nektar: Nektar Therapeutics. M. Tagliaferri: Advisory / Consultancy, Leadership role, Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Licensing / Royalties, Employed by Nektar: Nektar Therapeutics; Advisory / Consultancy, Travel / Accommodation / Expenses: Bluebird Bio. D.R. Spigel: Honoraria (institution), Research grant / Funding (institution): Abbvie; Honoraria (institution), Research grant / Funding (institution): Aeglea; Honoraria (institution), Research grant / Funding (institution): Amgen; Honoraria (institution), Research grant / Funding (institution): AstraZeneca; Honoraria (institution), Research grant / Funding (institution): Boehringer Ingelheim; Honoraria (institution), Research grant / Funding (institution): Bristol-Myers Squibb; Honoraria (institution), Research grant / Funding (institution): Celgene; Honoraria (institution): Evelo; Honoraria (institution), Research grant / Funding (institution): Foundation Medicine; Honoraria (institution), Research grant / Funding (institution): Genentech/Roche; Honoraria (self), Research grant / Funding (institution): GlaxoSmithKline; Honoraria (institution): Illumina; Honoraria (institution), Research grant / Funding (institution): Ipsen; Honoraria (institution), Research grant / Funding (institution): Lilly; Honoraria (institution), Research grant / Funding (institution): Merck; Honoraria (institution): Moderna Therapeutics; Honoraria (institution), Research grant / Funding (institution): Nektar; Honoraria (institution), Research grant / Funding (institution): Novartis; Honoraria (institution): PharmaMar; Honoraria (institution), Research grant / Funding (institution): Pfizer; Honoraria (institution), Research grant / Funding (institution): Takeda; Research grant / Funding (institution): Tesaro; Research grant / Funding (institution): Transgene; Research grant / Funding (institution): Neon Therapeutics; Research grant / Funding (institution): Transgene; Honoraria (institution): Armo; Honoraria (institution): Precision Oncology; Research grant / Funding (institution): Acerta; Research grant / Funding (institution): Astellas; Research grant / Funding (institution): CellDex; Research grant / Funding (institution): Clovis; Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution): EMD Serono; Research grant / Funding (institution): G1 Therapeutics; Research grant / Funding (institution): Grail; Research grant / Funding (institution): Millennium; Research grant / Funding (institution): OncoGenex. All other authors have declared no conflicts of interest.